Effect of quercetine on oxygen consumption under hypoxia - Yusupova, U; Djabbarova, G; Tukhtaeva, F; Olimova, Sh; Khaydarov, Sh (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
Quercetin reduces oxygen consumption in animals, reduces the effects of hypoxia on the body and prolongs life. Thus, quercetin increases the stability of cell and mitochondrial membranes, reduces physiological and biochemical processes in cells, shifts the body from an active metabolic state to a passive metabolic state.